2014 IEEE/AIAA 33rd Digital Avionics Systems Conference (DASC) 2014
DOI: 10.1109/dasc.2014.6979400
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing integrated terminal airspace operations under uncertainty

Abstract: In the terminal airspace, integrated departures and arrivals have the potential to increase operations efficiency. Recent research has developed geneticalgorithm-based schedulers for integrated arrival and departure operations under uncertainty. This paper presents an alternate method using a machine jobshop scheduling formulation to model the integrated airspace operations. A multistage stochastic programming approach is chosen to formulate the problem and candidate solutions are obtained by solving sample av… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…Typical approaches used for uncertainty optimization include stochastic programming, robust optimization, and chance-constrained optimization [22,23]. The most common applications of stochastic programming are the two-stage or multi-stage stochastic problems [24,25], where one assumes that the uncertain parameters can be represented by the known probability distribution based on complete knowledge of the uncertainty. The selection of the tackled problems for the stages are usually based on the prioritization of the particular information required.…”
Section: State Of the Artmentioning
confidence: 99%
“…Typical approaches used for uncertainty optimization include stochastic programming, robust optimization, and chance-constrained optimization [22,23]. The most common applications of stochastic programming are the two-stage or multi-stage stochastic problems [24,25], where one assumes that the uncertain parameters can be represented by the known probability distribution based on complete knowledge of the uncertainty. The selection of the tackled problems for the stages are usually based on the prioritization of the particular information required.…”
Section: State Of the Artmentioning
confidence: 99%
“…In addition to improving departure trajectory prediction with CDM gate pushback times and RNAV departure routing, arrival schedulers may use stochastic techniques to mitigate the uncertainty. Stochastic scheduling incorporates flight arrival-time uncertainty at the coordination point by including the probability of separation in the cost function [49][50][51][52]. If the flight scheduler cannot get an accurate 40minute advance gate pushback schedule from surface CDM, some system benefits may still be possible using flight plan departure times, even though surface scheduler assigned departure times would be much better.…”
Section: Mitigate Uncertaintymentioning
confidence: 99%
“…The performance of these two approaches was analyzed using data from Detroit (DTW) airport, and they concluded that, during peak times, the integrated approach provided an improved schedule, albeit at the cost of computational performance. Bosson et al (2015) generated a set of predefined paths for each aircraft, and developed an algorithm to compute optimal aircraft schedules and routes for 13 aircraft (using data from LAX airport). The major drawback of their model is that taxiway conflicts are not explicitly taken into consideration.…”
Section: Introductionmentioning
confidence: 99%